2007
DOI: 10.1111/j.1365-2958.2007.06008.x
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular location characteristics of the Pseudomonas aeruginosa GGDEF protein, WspR, indicate that it produces cyclic‐di‐GMP in response to growth on surfaces

Abstract: SummaryThe Pseudomonas aeruginosa Wsp signal transduction system produces cyclic-di-GMP (c-di-GMP), an intracellular messenger that stimulates biofilm formation and suppresses motility. The Wsp system is homologous to chemotaxis systems and includes a membrane-bound receptor protein, WspA, and a response regulator GGDEF protein, WspR, that catalyses c-di-GMP synthesis when phosphorylated. We found that the subcellular distributions of fluorescent protein-tagged WspA and WspR differed markedly from their chemot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
250
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 216 publications
(268 citation statements)
references
References 73 publications
9
250
0
2
Order By: Relevance
“…This differential activity could be attributable to a number of factors, including growth on a surface, density of the culture, oxygen concentration, or degree of agitation. Surface activation of a DGC has been described previously because the DGC WspR from P. aeruginosa forms active clusters when grown on a solid surface (25). This observation further highlights the importance of quantifying c-di-GMP and phenotypic output from identical growth conditions.…”
Section: Resultsmentioning
confidence: 72%
“…This differential activity could be attributable to a number of factors, including growth on a surface, density of the culture, oxygen concentration, or degree of agitation. Surface activation of a DGC has been described previously because the DGC WspR from P. aeruginosa forms active clusters when grown on a solid surface (25). This observation further highlights the importance of quantifying c-di-GMP and phenotypic output from identical growth conditions.…”
Section: Resultsmentioning
confidence: 72%
“…3A). WspR, which is involved in c-di-GMP synthesis in response to surface contact (15,17), had no role in the Psl response (Fig. S3).…”
Section: Resultsmentioning
confidence: 99%
“…We initially targeted our analysis to three diguanylate cyclases that have been strongly linked to P. aeruginosa biofilm formation: SadC, SiaD, and WspR (15,16,28). Using directed mutagenesis, we demonstrated that SadC and SiaD both contribute to Pslinduced c-di-GMP production (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…WspR consists of a CheYlike phospho-receiver domain and a GGDEF domain that has DGC activity in vivo and in vitro (D'Argenio, 2002;Hickman, 2005;Güvener, 2007). WspR is a response regulator encoded by the wsp operon (wspABCDEFR), which comprises a multi-component chemosensory system with homology to the well-characterized chemotaxis (Che) pathway of E. coli (Ridgway, 1977;D'Argenio, 2002;Güvener, 2007).…”
Section: Wsp Chemosensory Systemmentioning
confidence: 99%